Gadolinium blocks membrane permeabilization induced by nanosecond electric pulses and reduces cell death - André, Franck M. (2009)
It has been widely accepted that nanosecond electric pulses (nsEP) are distinguished from micro-and millisecond duration pulses by their ability to cause intracellular effects and cell death with reduced effects on the cell plasma membrane. However, we found that nsEP-induced cell death is most likely mediated by the plasma membrane disruption. We showed that nsEP can cause long-lasting (minutes) increase in plasma membrane electrical conductance and disrupt electrolyte balance, followed by water uptake, cell swelling and blebbing. These effects of plasma membrane permeabilization could be blocked by Gd(3+) in a dose-dependent manner, with a threshold at sub-micromolar concentrations. Consequently, Gd(3+) protected cells from nsEP-induced cell death, thereby pointing to plasma membrane permeabilization as a likely primary mechanism of lethal cell damage.